The Efficacy of Using Pair Work Technique in Teaching Conditional Sentences to Indonesian English as Foreign Language (EFL) Students - Soleman Dapa Taka (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This research aims at finding out the efficacy of using the pair work technique in teaching grammar especially the conditional sentences to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of the pair work technique effective in teaching conditional sentences to Indonesian EFL students?.  The research can be an addition to the persisting teaching grammar of English particularly the conditional sentences through the use of the pair-work technique.  This research was conducted at the tenth-grade students at SMA Kristen Mercusuar Kupang, an Indonesian High School. The total number of samples was 25 students. The research used a pre-experimental method with a pre-test and post-test design. The pre-test was given to find out the basic ability of the students in mastering conditional sentences and the post-test given to find out the students’ improvement in mastering conditional sentences after giving the treatment by using of pair work technique. The findings show that using the pair work technique is effective in teaching conditional sentences to Indonesian EFL students. It is supported by the result of the significance test through SPSS 20 program that the P was 0.00.  Therefore, it is recommended to use the pair work technique in developing students’ competence in mastering conditional sentences l of Indonesian EFL students.